Highly stretchable dielectric elastomer composites containing high volume fractions of silver nanoparticles1. Issue 28 (28th July 2015) - Quinsaat, Jose Enrico Q.; Alexandru, Mihaela; Nüesch, Frank A.; Hofmann, Heinrich; Borgschulte, Andreas; Opris, Dorina M.
<x xml:space="preserve">Abstract</x> A composite of Ag/SiO2 core–shell nanoparticles 20 vol% in polydimethylsiloxane with ε′ = 5.9, Eb = 13.4 V μm−1, Y100% = 350 kPa, and a strain at break of 800% is presented.